Sago (metroxylon sagu rottboll), the forgotten palm - Chew, Tek-Ann; Md. Isa, Abu Hassan bin; Mohayidin, Mohd. Ghazali bin (Informa UK Limited, 1999)
Sago (Metroxylon sagu Rottboll) is a remarkably hardy plant that is indigenous to South East Asia. This palm thrives in waterlogged, acidic soils where few other plants survive. Sago is an important source of carbohydrates for the local inhabitants and is the crop par excellence for sustainable agriculture. However, owing to the introduction of more profitable crops like rice and oil palm, the areas under sago in Malaysia have declined dramatically over the years. The only large areas remaining under sago now are in the state of Sarawak. In this paper, the present status of sago palm in Malaysia is reviewed and the prospects and possibilities of its emergence as a major crop are discussed. The future prospects for sago are bright if the appropriate policy measures are undertaken.